Towards an Editable, Versionized LOD Service for Library Data - Ostrowski, Felix; Pohl, Adrian (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2013)
The Northrhine-Westphalian Library Service Center (hbz) launched its LOD service lobid.org in August 2010 and has since then continuously been improving the underlying conversion processes, data models and software. The present paper first explains the background and motivation for developing lobid.org . It then describes the underlying software framework Phresnel which is written in PHP and which provides presentation and editing capabilities of RDF data based on the Fresnel Display Vocabulary for RDF. The paper gives an overview of the current state of the Phresnel development and discusses the technical challenges encountered. Finally, possible prospects for further developing Phresnel are outlined.